A new stenoendemic species of Blephilia (Lamiaceae: Lamioideae; Menthinae) from the Interior Low Plateau of Tennessee - Floden, Aaron; Schilling, Edward E. (Phytotaxa, 2020)
A new species of Blephilia, B. woffordii sp. nov., is described and illustrated based on results of morphometric and molecular analyses. The results support the distinctiveness of four species of Blephilia. The newly recognized species is distributed on limestone bluffs and cliffs within a small section of the Caney Fork River drainage of Middle Tennessee in the Eastern Highland Rim physiographic province. This region is known for several endemic species and also several species disjunct from the Ozark region of the Interior Highlands. A revised key to the genus is provided.